2021
DOI: 10.21203/rs.3.rs-333649/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Coping with homeschooling and caring for children during the UK COVID-19 lockdown: voices of working mothers 

Abstract: We examined working mothers’ experiences and feelings about homeschooling and caring for children while working during the summer 2020 COVID-19 lockdown in the UK. Eligible mothers were invited to participating in an on-line survey of open-ended questions that was distributed via social media between mid - June to mid-August 2020. Participants (n = 47; Mage = 39.6, range = 28 to 54 years) were predominantly white married working mothers and most had a higher education degree. The experience of combining homesc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…In this context, the experience of the confinement and its consequences might have been more challenging for children with SEN and their families. A growing body of research has shown that caregivers with children with SEN/D found caring for their children during the lockdown difficult (Castro-Kemp and Mahmud, 2021;Kallitsoglou and Topalli, 2021). As expected, we also found that caregivers with children with SEN reported significantly high rates of family co-existence difficulty.…”
Section: Discussionsupporting
confidence: 81%
“…In this context, the experience of the confinement and its consequences might have been more challenging for children with SEN and their families. A growing body of research has shown that caregivers with children with SEN/D found caring for their children during the lockdown difficult (Castro-Kemp and Mahmud, 2021;Kallitsoglou and Topalli, 2021). As expected, we also found that caregivers with children with SEN reported significantly high rates of family co-existence difficulty.…”
Section: Discussionsupporting
confidence: 81%
“…Yet, challenges arose during the pandemic as schools had to communicate with SEN children by remote and digital means, with "rapid changes of teaching formats" (Nusser, 2021, p. 59). Support of this kind could be variable (Kallitsoglou & Topalli, 2020), and ACER (2020) reported that the majority of schools failed to give parents individualised learning instructions, and resources sent home were mostly worksheets.…”
Section: Inclusive Differentiated Digital Provision During Lockdownmentioning
confidence: 99%
“…Even amongst mothers who did not lose jobs, early research suggests women were uniquely affected by increased childcare demands (Andrew et al, 2020c;Kallitsoglou & Topalli, 2021;Minello et al, 2020). These demands give new meaning to the idea that "home becomes work" from Hochschild's (1997) study of the "time bind."…”
Section: How Covid−19 Has Affected Work and Homementioning
confidence: 99%
“…This increased stress manifests specifically in terms of elevated rates of anxiety and depression among parents of small children (Brown et al, 2020). In Germany, Czymara et al (2021) found that women are worrying considerably about the well-being of home and family (Kallitsoglou & Topalli, 2021), whereas men are worried about employment and the economy far more. Mothers in Iceland also reported feeling "overwhelmed, frustrated, tired, annoyed, and angry" (Hjálmsdóttir & Bjarnadóttir, 2021, p. 274) with having to manage others' fears and anxieties during the pandemic; and for a country at the top of the gender equity scale, mothers were frustrated with the lack of support.…”
Section: How Covid−19 Has Affected Work and Homementioning
confidence: 99%
See 1 more Smart Citation